2014
DOI: 10.1002/smll.201401895
|View full text |Cite
|
Sign up to set email alerts
|

Broadband Metallic Absorber on a Non‐Planar Substrate

Abstract: Absorbers for visible and near-infrared light are realized by depositing a thin iron layer on arrays of cones which are replicated from a porous template. The replicated conic structure itself is of several micrometers and ineffective at antireflection, but the subsequent deposition of iron on top generates nano-meter-size columnar structures, and thus broadband absorption enhancement is achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…The high pumping irradiance, necessary for efficient energy conversion, makes the practice of TC and TPV devices particularly challenging in terms of cost, efficiency and reliability. It is believed that significant improvements in those areas can be made by designing a nearly perfect electromagnetic energy absorber that can achieve broadband, wide-angle and polarization-independent absorption 15 16 17 18 19 20 21 22 23 24 25 26 27 , as well as excellent photothermal properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The high pumping irradiance, necessary for efficient energy conversion, makes the practice of TC and TPV devices particularly challenging in terms of cost, efficiency and reliability. It is believed that significant improvements in those areas can be made by designing a nearly perfect electromagnetic energy absorber that can achieve broadband, wide-angle and polarization-independent absorption 15 16 17 18 19 20 21 22 23 24 25 26 27 , as well as excellent photothermal properties.…”
mentioning
confidence: 99%
“…With the rapid advent of nanotechnology, design of highly-efficient and compact antireflection coatings or surface absorbers has become viable using nanophotonic techniques: photonic nanostructures 18 19 20 21 22 23 24 25 26 27 28 29 , photonic crystals 30 31 , and metamaterials 15 16 17 . Aiming to facilitate the use of TC and TPV energy conversion devices, here we develop a simple and cost-effective chemical route to prepare a high-performance, large-area absorber constructed using a nanoporous alumina film on top of the commercial 6061-T6 aluminum (Al) substrate.…”
mentioning
confidence: 99%
“…A strong stray light will reduce star image quality and signal to noise ratio. For safeguarding optical instruments present on the satellites and to suppress stray light, various types of black coatings are developed in past few years . Most of these black surfaces are fabricated using surface texturing, optical grating, etching, nano composite or by applying coating of different nanomaterials on the surface of interest.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to their limitations such as narrow bandwidth, complex structure, and costly fabrication routes, these absorbers find limited application. To overcome these issues, efforts have been made to fabricate near perfect optical absorber coating using nanomaterials . Among these, carbon‐based nanomaterials finds huge potential in the fabrication of ultra‐black absorbers due to their exciting combination of properties .…”
Section: Introductionmentioning
confidence: 99%
“…A super absorber should ideally have extremely low reflectance ( R < 0.2%) and very high absorption (A > 99%) over broadband frequency range and angle of incident beam 5 .Various processes as well as materials have been developed to bring down the refractive index of objects to unity and thus increase their absorption capacity 6 9 . It is reported that introduction of hierarchal micro-nano structures leads to a near perfect absorber 10 12 . The absorbing frequency range of these hierarchal structures depend on the number of factors including refraction index, texture shape, size and their arrangement in the material microstructure 13 .…”
Section: Introductionmentioning
confidence: 99%